Brand Response of Cell-phone Users in Nepal: A Strategic Perspective - Sthapit, Arhan; Shakya, Darshan Bir (PYC Nepal Journal of Management, 2010)
In view of the rapidly expanding cell-phone market, the authors inquired into buyer brand behaviour to draw important inputs for strategies in Nepal. By researching into 140 buyers selected through a cluster sampling technique for four recent months, the study has sought to examine buyer response (preference and loyalty) towards established global brands (EGBs) and emerging Chinese brands in Nepali cell-phone market, a 4-billion rupees business. The study has inferred that brand loyalty is almost non-existent while Nepali buyers have shown extremely high preference for Nokia, an established global brand. Price and efficiency are the key factors behind buyers’ brand selection while new technology and features most influenced cell-phone purchase decisions. The authors suggested strategies not only of advertising and brand promotion but also of brand-tracking on critical KPIs (key performance indicators) of the brand, and benchmarking.